The Role of Standard-Setting Organizations with Regard to Balancing the Rights Between the Owners and the Users of Standard-Essential Patents - Randakeviciúte, Jurgita (Munich Intellectual Property Law Center - MIPLC, 2015)
Standard-setting is an essential tool for promoting innovation, competition and resulting in benefits to consumers and businesses. However, due to the fact, that standards are usually protected by standard-essential patents (SEPs), standard-setting may obstruct the access to the standardized technology and create entry barriers into the market for those, who do not own SEPs. The afore-described events cause tension between the owners and the users of SEPs. In order to keep the balance between the afore-specified parties, standard-setting organizations (SSPs) come into play by requiring SEPs owners to license these patents on fair, reasonable and non-discriminatory (FRAND) terms. Nevertheless, the latter attempt quite often results in costly and time-consuming litigation, because the parties are not able to agree what kind of terms are FRAND. Such situation inevitably impedes the implementation of the standardized technology into industries and calls for a re-consideration of the role of SSOs during the process of standardization and after the standard is set. In this work, the possible role of SSOs while improving the access for the users to the standardized technology will be discussed.